Instagram Role In Influencing Youth Opinion In 2015 Election Campaign In Bahrain - Amira Karam Eldin (European Scientific Journal, ESJ, 2016)
This study can be considered a descriptive study portraying the effect of the exposure to Instagram campaign in Bahrain among Bahrainis. The research is mainly concerned with presenting this effect in relevance to their awareness, attitude, and behaviour. Its main question: Does the exposure of the studied sample to Instagram election campaigns; has an effect on their cognitive, affective and behavioural systems? A self-administrated questionnaire was distributed to 200 Bahraini universities youth to know cognitive, affective and behavioural levels of awareness and changes. The researcher main objective was to know the effect of Instagram in the latest election in Bahrain (2015) and whether it encouraged people to vote and feel the importance of their vote. In addition to understand the level of awareness of each candidate and the information they knew through Instagram. The results proved the effectiveness of Instagram to get to the youth as the rate of seeing Instagram election post per week, 62.16% of the questionnaire takers answered that they see it more than 9 times a week, 8.10% see it 7 – 9 times a week, 16.21% see it 4 – 6 times a week, and 13.51% see it 1 – 3 times a week. 8.10% of the participants said that they “always” get information about the election candidates & their programs from the Instagram election posts, 21.62% said that they “frequently” do, 37.83% said “sometimes”, 21.62% said “rarely”, and 10.81% said they “never” do get information about the election candidates and their programs from Instagram election posts.